Idiosyncratic Shocks, Child Labor and School Attendance in Indonesia - Bayu Kharisma (International Journal of Evaluation and Research in Education (IJERE), 2017)
This paper investigates the effect of various idiosyncratic shocks against child labor, child labor hour and school attendance. Also, the role of the assets held by households as one of the coping strategies to mitigate the effects of shocks. The results show that various idiosyncratic shocks that encourage child labor is generally caused by crop loss, a disease suffered by the head or member of the household, a decrease in household income due to lower prices and the quantity produced and the death of the head or a family member. This indicates that households are not sheltered from the idiosyncratic shocks and restricted access to formal and informal institutions. Other findings show a variety of idiosyncratic shocks does not affect child labor hour and the school attendance. Additionally, household assets play an important role in reducing the number of child labor and increase school attendance but do not affect the child labor hour during a variety of idiosyncratic shocks.